Reaksi Pasar Modal Terhadap Pengumuman Right Issue pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Amir, Pita Qurnia; Suaryana, I. G. N. Agung (E-Jurnal Akuntansi; Vol 28 No 1 (2019)DO - 10.24843/EJA.2019.v28.i01.p07, 2019)
This research aims to determine whether there is a market reaction to the announcement of the rights issue. This research was conducted on the Indonesia Stock Exchange (IDX) in publicly listed companies that conducted rights issues during the period 2011-2017 with a population of 143 companies. The sample selection uses non-participant observation method with purposive sampling technique, obtained a sample of 103 companies. The analysis technique used is to test one sample t-test on the cumulative abnormal return. Based on the results of the analysis conducted, it was found that there is no market reaction to the announcement of the rights issue, which means the announcement of the rights issue does not have information content so it does not affect the investor's preference in making decisions. Keywords : Right issue, abnormal return, market reaction.